Juridical Review of Landreform Land Object Redistribution in Bantarsari Village, Cilacap Regency - Giovanni Helmi Munif (UMPurwokerto Law Review, 2021)
Land reform is defined as an effective way to achieve successful development because access to land is crucial for socio-economic development, poverty alleviation, and environmental sustainability. Apart from being a factor of production, the land is also a factor of wealth and prestige. And strength or power. Bantasari Village, Bantarsari Sub-District, Cilacap District is one of the villages that conducts land object redistribution activities in land distribution and land certificates issuance. The redistribution of land objects has not been optimal, and this is because there are still many residents who do not have land certificates as proof of ownership. This research discusses how the juridical review and constraints in implementing land reform land objects' redistribution in Bantasari Village, Bantarsari Sub-District, Cilacap District based on Presidential Regulation No. 86/2018. The method used in this study is the normative juridical method used. It came out through literature studies examining secondary data. The implementation of Agrarian Reform referred to in Article 5 paragraph (1) Presidential Regulation Number 86 of 2018 concerning Agrarian Reform including those carried out through the stages of wealth management referred to in Article 5 paragraph (1) letter a consists of land redistribution or asset legalization.Keywords: Land Redistribution, Land reform, certificate